The Influence of Training and Organizational Culture on Employee Performance at BRI Singaraja Branch with Work Motivation as a Mediating Variable - Yuliani, Made Risma; Kadek Rai Suwena; Made Ary Meitriana (JURNAL MANAJEMEN MOTIVASI, 2026)
The continuous expansion of banking services and facilities demands that frontliner personnel, who serve as the institution’s primary point of contact, adjust quickly so they can deliver information correctly and reliably. This research aims to analyze how training and organizational culture are associated with staff performance at BRI Singaraja, while positioning work motivation as an intervening factor. A quantitative descriptive approach was applied in this research. The findings reveal that training contributes positively and significantly to the work motivation of employees at BRI Singaraja Branch. In addition, organizational culture also shows a positive and significant contribution to the motivation of frontliner staff at the same branch. Training was further found to improve employee performance in a positive and significant manner, and work motivation likewise demonstrated a positive and significant role in enhancing employee performance. Moreover, training was shown to influence performance indirectly through work motivation, and organizational culture also affected performance indirectly through the same intervening variable. Based on these findings, both training and organizational culture can be understood as important determinants of employee performance, with work motivation acting as the intermediary mechanism that connects the independent factors to the dependent outcome.